439 A Colloidal Polymethyl-Methacrylate (PMMA) Microsphere-Based Treatment for Patients with Symptomatic Discogenic Disease: A Safety and Feasibility Clinical Trial. (1st April 2022) - Brown, Nolan J.; Shahrestani, Shane; Lien, Brian; Yang, Chen Y.; Ton, Emily; Diaz-Aguilar, Luis D.; Sahyouni, Ronald; Wali, Arvin R.; Abraham, Mickey E.; Taylor, Sandra; Taylor, William R.
Abstract : INTRODUCTION: Low Back Pain (LBP) is a global healthcare issue, and first line therapy for patients with LBP include physical therapy, oral pain relievers, and steroid injections. If unsuccessful, surgical procedures are indicated. Non-surgical second-line treatments for LBP are warranted, and one example is DiscSeal, a colloidal form of viscous gel composed of polymethyl-methacrylate microspheres and aqueous buffered sodium hyaluronate. METHODS: Six participants were enrolled. The study population comprised of males/females between the ages of 18 and 70, diagnosed with chronic LBP of six months or more prior to enrollment determined to be predominantly caused by discogenic disease of the lumbar spine who failed at least six weeks of conservative management. Participants completed visits at 7, 14, 42, 90, and 180 days. RESULTS: The mean age of participants was 38.8 ± 10.0 years. The mean DiscSeal volume administered was 1.62 ± 0.35 mL with a range between 1.1-2.0 mL. The mean procedure time was 10.8 minutes. Mean LBP visual analog scale (VAS) percentage changes from baseline were -27.0% at 90 days and -42.3% at 180 days, with 50.0% of participants maintaining LBP VAS scores <4 at 90- and 180-days post treatment with DiscSeal. Similarly, mean leg pain VAS percentage changes from baseline were -47.0% at 90 days and -36.6% at 180 days. Overall, participants' average improvement, assessed by Patient Rating Overall Health Status, was 55.2% at 90 days and 67.8% at 180 days. CONCLUSION: The results from this first-in-man trial suggest a favorable safety and efficacy profile for the continued study of DiscSeal. Future studies evaluating DiscSeal as a minimally invasive therapy for chronic discogenic LBP are warranted.